Large dams and small reservoirs: co-modeling water storage strategies in a Mediterranean catchment under a changing climate - Villani, Lorenzo; Castelli, Giulio; Forzini, Eleonora; Piemontese, Luigi; Lucca, Enrico; Bouizrou, Ismail; Lompi, Marco; Bertoli, Gabriele; Giuliano, Alessandro; Chiarelli, Davide Danilo; Theodotou Schneider, Xenia; Pacetti, Tommaso; et al. (Frontiers in Water, 2025)
The Mediterranean water sector faces multiple challenges. Climate change not only drives future water shortages but also drastically affects the effectiveness of water storage strategies, such as small and large reservoirs. Furthermore, the limited involvement of local actors often hampers the success of implemented solutions. We apply a co-modeling approach within the Val d'Orcia Rural Living Lab, to inform water planners about the potential impacts of climate change on reservoir water dynamics and to nourish the discussion on climate change adaptation. Specifically, we simulate various water storage strategies by alternatively considering existing small agricultural reservoirs (SmARs) and a planned large dam under current and projected future climates considering five climate models under the Shared Socioeconomic Pathway 585. Due to the reduced precipitation and increased temperature, future annual average water stored in both types of reservoirs is expected to decline (−6.3%) as a result of limited inflows (−30%) and enhanced evaporation (8.7%) by the end of the century. Moreover, seepage losses decrease (−9.8%) reducing aquifer recharge. While the trends in these key variables are consistent across storage types, SmARs are more susceptible to climate change, with water storage reductions of up to −21%. Evaporation losses increases are a major concern for the dam, whereas the reduction of inflows poses a major threat to the reliability of the smaller SmARs. Still, SmARs have several advantages and a more comprehensive and participatory analysis is important for appropriate decision-making. By involving local actors from the early stages, this research poses the basis for developing future best watershed management practices within a representative Mediterranean catchment.